STRATEGI KOMUNIKASI PRAJURU DALAM MEMILIH PRAWAYAH DI DESA ADAT TIMBRAH KABUPATEN KARANGASEM - I Made Bagiarta Mandraguna; I Gusti Ngurah Sudiana; Ida Bagus Gede Candrawan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
ABSTRACT Prajuru Timbrah Traditional Village has difficulty choosing prawayah. This obstacle made prajuru have to carry out a communication strategy. How this communication strategy is carried out in selecting interesting prawayah for further research. This thesis research takes the title